Hubungan Antara Dukungan Orang Tua dengan Gangguan Komunikasi pada Anak Autisme Spectrum Disorder di Pusat Layanan Disabilitas dan Pendidikan Inklusi Kota Surakarta - DEWI SYAH FITRI, ANISYAH; DHIA SALSABILA, NISRINA (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2024)
Parental social support greatly affects the development of children with autism disorders, providing appropriate social support is expected to optimize their needs and improve their quality of life. The research method uses quantitative research with correlation design and uses a cross-sectional data collection time approach method. In sampling using purposive sampling technique as many as 28 children. Based on the results of the analysis that has been done from 28 respondents. The results of the parental support questionnaire showed that 21 respondent parents provided social support in the good category with a percentage of 75.0%. 4 respondent parents provided social support in the sufficient category with a percentage of 14.3% and 3 respondent parents provided low category social support. Expressive language ability from the results of the Verbal Expressive Vocabulary Test (TKVE) showed that 24 children got an average score with a percentage of 85.7% and 4 children got low with 14.3%. Based on the results of the data analysis, it can be concluded that there is a relationship between Parental Support and Expressive Language Ability of Autism Spectrum Disorder children aged 4-6 years at PLDPI Surakarta City.